Analisis Transformasi Digital Pelayanan Publik Menggunakan Metode Gartner Analytic Asceedency (Studi Kasus : Pelayanan Perizinan Pemerintah Daerah Kabupaten Majene - Aulia Rahman; Dian Megah Sari; Farid Wajidi (Jurnal Komputer Terapan, 2023)
Public service is one of the activities carried out to fulfill the need for services to the community or individuals. With the outbreak of the Covid-19 virus some time ago, it demands public service delivery to innovate so that public services can run well and optimally even in a situation of physical distancing. One of the innovations was utilizing technology or digital transformation in public services. The aim of this study is to analyze the role and influence of digital transformation in improving licensing services in Majene Regency through the use of the Online Single Submission (OSS) application and the SiCantik Cloud application. The method used in this study is explanatory research with analytical techniques using Gartner Analytic Ascendency. The results of this study indicate that the Regional Government of Majene Regency needs to take persuasive approaches to remove existing obstacles to the use of digitalization in licensing services, such as regulating the use of regional digital-based licensing services in a binding regulation, conducting thorough education for users of licensing services, conduct outreach regarding the importance of this digital-based licensing service and expand the reach of fixed broadband and mobile broadband networks in Majene Regency. These things can be done by involving the cooperation of related agencies such as the Investment and One-Stop Integrated Services (DPMPTSP) and Communication, Information, Statistics and Coding Services (Dinas Kominfo) of Majene Regency.